Effectiveness of Patching in Correcting Refractive Errors in Cases with Anisometropic Amblyopia - Aykut Arslan Yıldız; Yavuz Bardak (Türk Oftalmoloji Dergisi, 2011)
Pur po se: To evaluate the effects of patching on refractive errors in patients with anisometropic amblyopia. Ma te ri al and Met hod: We evaluated retrospectively 81 cases (5-8 years old) which were applied patching treatment for unilateral anisometropic amblyopia between June 2005 and August 2009. Pre- and post-treatment visual acuities and stereopsis were evaluated and the cases were divided into 4 groups as hyperopia, hyperopic astigmatism, myopia, and myopic astigmatism. Re sults: Mean age was 6.8±0.1 (minimum-maximum: 5-8) years. Visual acuity was 0.57±0.07 log MAR in hyperopias (p=0.001), 0.74±0.07 logMAR (p=0.001) in hypermetropic astigmatisms, 0.1±0.02 log MAR (p=0.02) in myopias, and 0.62±0.08 logMAR (p=0.04) in myopic astigmatisms after treatment. Post-treatment stereoacuity was improved significantly, except for myopic astigmatism (p=0.1). Dis cus si on: Patching treatment in anisometropic amblyopia is safe and effective method in all refraction errors especially hyperopia. (Turk J Ophthalmol 2011; 41: 385-8)